Penerapan Model Pembelajaran Kooperatif Tipe Jigsaw pada Pembelajaran IPA Kelas V SD Negeri Suka Menang - Listia Nurbaiti; Ahmad Gasdy Prananosa; Tri Juli Hajani (Journal of Elementary School (JOES), 2023)
This study aims to determine the student's IPA learning outcomes after applying the Cooperativ Tipe JIGSAW model for class V SD Negeri Suka Menang. The method used is in the form of an experiment with an experimental design used one-group pre-test and post-test. In this study, one sample class was used, namely all fourth grade students of SD Negeri Suka Win, totaling 20 students. The data collection technique used is a test technique. The collected data were analyzed using the z-test. Based on the results of data analysis with a significant level of = 5% and dk = 19, it shows the magnitude of Zcount = 7,62 and Ztable = 1.64 (Zcount>Ztable). Thus, it can be concluded that the IPA learning outcomes of V grade students of SD Negeri Suka Menang after the implementation of the Cooperativ Tipe JIGSAW significantly completed. Keywords: Application, JIGSAW, IPA,